Pengaruh Retrofit Refrigeran CFC-12 Dengan HCR-12 Terhadap Kinerja Refrigerator Domestik dan Perawatannya - Isnanda Isnanda; Yazmendra Rosa; Elvis Adril; Feidihal Feidihal (Politeknik Negeri Padang, 2019)
In the recent years,almost every house, has domestic refrigerator wich still use CFC-12 refrigerant as the fluid.When the leakage happen, the refrigerant causes the demage of ozon such as forming the ozon side then radiation of ultra violet from the sun ray in high intensity reach the surface on each directly and it is dangerous for the human life. The Hidrocarbon refrigerant (HCR-12) is considered as one of alternative, wich is environmentally friendly,more energy to save and without modification, to replace the CFC-12.This research compare the performance of household refrigerator using the CFC-12 refrigerant and HCR-12 without the modification of refrigerator.The result shown from the COP, that the refrigerators work for both of refrigerant is relatively the same and the quality of the ice product from HCR-12 is better than CFC-12, because the amount of the energy wich is absorbed by HCR-12 during the evapouration process is bigger than CFC-12. Analyzing the amount of refrigerant weight fullfilled to refrigerator, HCR-12 only uses 40 % from CFC-12,If the price of both refrigerant is the same,the use of HCR-12 is profitible than the use of CFC-12